Atmospheric ozone at South Pole, Antarctica, in 1986 - Komhyr, W. D.; Oltmans, S. J.; Grass, R. D. (1988)
Results of NOAA's measurements of the ozone vertical distributions at the South Pole and of the annual course of total ozone, conducted in 1986 with balloon-borne electrochemical concentration cell (ECC) ozonesondes and a Dobson spectrophotometer, are described. The major finding was that the stratospheric ozone decreases abruptly between September 20 and October 15, with the bulk decrease occurring between 12 and 21 km. In this period, the column ozone and ozone volume mixing ratio at 16 km (the altitude of the normal ozone maximum at South Pole) decreased by 78 percent, and column ozone between 12 and 21 km decreased by 50 percent. The results of these measurements are compared with data obtained in 1971, and the changes observed in the ozone vertical distributions and in the temporal variations of atmospheric ozone are discussed.